Teori Taxonomi Bloom Dan Implementasinya Dalam Pembelajaran Pendidikan Agama Islam - Azizah, Kamilatin (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2025)
Islamic education is a means of making humans fit to live in the world, able to act according to religious norms, behave in a noble manner, and always be devoted to Allah SWT. To achieve the goals of Islamic education, improvements are needed in the educational process, including techniques, materials, strategies and evaluation in learning. With regard to learning evaluation, there are three domains that are measured in student assessment, namely cognitive, affective and psychomotor, known as Bloom's Taxonomy theory. This article discusses the old version of Bloom's taxonomy theory and the results of its revision and implementation in Islamic religious education learning. This research uses a qualitative method, a type of literature study. The data collection method uses documentation from relevant books and journals. The aim of this research is to describe Bloom's taxonomy theory and its implementation in Islamic religious education (PAI). The research results in this article describe the history of the development of Bloom's taxonomy theory, outline Bloom's taxonomy and Bloom's revised taxonomy theory. Next, it describes the implementation of Bloom's taxonomy theory in PAI learning, where the emphasis is placed on evaluating and assessing learning. Apart from being a means of expanding scientific disciplinary literature, the research results are intended for educators, especially PAI educators, to evaluate student learning achievements in accordance with correct developmental theory so that assessments become more valid and focused.